2008
DOI: 10.3174/ajnr.a1007
|View full text |Cite
|
Sign up to set email alerts
|

Tract-Based Spatial Statistics of Diffusion Tensor Imaging in Adults with Dyslexia

Abstract: BACKGROUND AND PURPOSE:Diffusion tensor imaging is a tool that can be used to study white matter microstructure in dyslexia. We tested the hypothesis that dyslexics have a white matter structural change (as measured by directional diffusion of water, which can be affected by disruption in white matter tracts) between brain regions that previous functional connectivity studies showed were associated with phonologic processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 23 publications
5
55
1
Order By: Relevance
“…As previously mentioned, Richards et al (2008) found greater FA in the left and right cerebellum in a group of individuals with dyslexia relative to typical readers. This study was limited by lack of regional segmentation but it represents an important area for future research.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…As previously mentioned, Richards et al (2008) found greater FA in the left and right cerebellum in a group of individuals with dyslexia relative to typical readers. This study was limited by lack of regional segmentation but it represents an important area for future research.…”
Section: Introductionsupporting
confidence: 74%
“…In the only published DTI study which included the cerebellum, Richards et al (2008) also conducted a whole-brain DTI study of fathers of children in a familial study of dyslexia, 14 with dyslexia and 7 without dyslexia. Typical readers had greater FA in language-related white matter tracts (28 bilateral frontal, temporal, parietal, and occipital areas as defined by Anatomical Automatic Labeling (AAL) atlas boundaries and an additional 7 by DTI atlas boundaries).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of neuroanatomy, some studies have reported a reversal of asymmetry (RH larger than LH) in the planum temporale in individuals with RD, although the evidence for this is somewhat mixed (Geschwind & Levitsky, 1968; Hynd, Semrud-Clikeman, Lorys, Novey, & Eliopulos, 1990; Larsen, Høien, Lundberg, & Odegarrd, 1990; Rumsey et al, 1997; Schultz et al, 1994). Reduced gray and white matter development in LH regions for RD readers have also been frequently reported (e.g., Beaulieu et al, 2005; Deutsch et al, 2005; Eckert, 2004; Keller & Just, 2009; Klingberg et al, 2000; Niogi & McCandliss, 2006; Richards et al, 2008; Rollins et al, 2009). …”
Section: Introductionmentioning
confidence: 75%
“…There are first reports suggesting abnormalities of the left hemisphere tracts that connect occipito-temporal brain regions engaged by visual-orthographic processes with temporo-parietal and the left inferior frontal areas engaged by phonological processes (e.g. Beaulieu et al, 2005;Deutsch et al, 2005;Richards et al, 2008). Consistent with impaired phonological-orthographic connectivity in dyslexic readers are functional imaging findings-some with German dyslexic readers van der Mark et al, 2009;Wimmer et al, in press)-which showed reduced reading-related activation in a left ventral occipito-temporal brain region, which is assumed to function as interface between high-level visual orthographic codes and phonology and meaning.…”
Section: A New Hypothesis: Dyslexia Resulting From Reduced Orthographmentioning
confidence: 99%